2010
DOI: 10.3109/02699200903450164
|View full text |Cite
|
Sign up to set email alerts
|

Phonological processes in Kannada-speaking adolescents with Down syndrome

Abstract: Phonological process analysis was carried out using a 40-word imitation task with 30 11;6-14;6 year old Kannada-speaking persons with Down syndrome in comparison with 15 non-verbal mental age matched typically developing children. Percentages of occurrence were significantly higher for the Down syndrome group with certain exceptions. Some phonological processes were observed only in the Down syndrome group. Kannada is a non-Indo European language spoken in the southern Indian state of Karnataka that has not ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Assessments of phonological development in DS populations are mainly based on two elicitation methods: tests of articulation (Dodd, 1976;Van Borsel, 1988, 1996Roberts et al, 2005;Rupela et al, 2010); spontaneous or connected speech (Stoel-Gammon, 1980;Barnes et al, 2009); and sometimes on a combination of both an articulation test and spontaneous speech (Sommers et al, 1988;Parsons and Iacono, 1992;Yousif, 2018;Hidalgo de la Guía and Garayzábal, 2019). Studies indicate a higher frequency of phonological processes in connected speech, but only Yousif (2018) reports some evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Assessments of phonological development in DS populations are mainly based on two elicitation methods: tests of articulation (Dodd, 1976;Van Borsel, 1988, 1996Roberts et al, 2005;Rupela et al, 2010); spontaneous or connected speech (Stoel-Gammon, 1980;Barnes et al, 2009); and sometimes on a combination of both an articulation test and spontaneous speech (Sommers et al, 1988;Parsons and Iacono, 1992;Yousif, 2018;Hidalgo de la Guía and Garayzábal, 2019). Studies indicate a higher frequency of phonological processes in connected speech, but only Yousif (2018) reports some evidence.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the existence of such representations can contribute to a faster elimination of phonological errors and to a faster development of the phonological mechanism in Down syndrome (Dodd & Thompson, 2001; Eadie et al, 2002; Nash & Snowling, 2008). Generally, though, phonological distinctness in children with Down syndrome becomes apparent from their first word utterances (Abbeduto et al, 2007; Kent & Vorperian, 2013; Kumin, 2006; Stray‐Gunderson, 1986), since phonological errors are very common at preschool and early school age in Down syndrome (Andreou & Katsarou, 2015; Kumin, 2008; Laws, 2004; Rosin et al, 1988; Rupela et al, 2010; Yoder et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In people with Down syndrome the differentiation in phonology becomes apparent even from their very first utterance of words (Abbeduto et al, 2007; Kent & Vorperian, 2013; Kumin, 2006; Stray‐Gunderson, 1986). Phonological errors are very common at preschool and early school age in children with Down syndrome, when generally low phonological development is observed (Andreou & Katsarou, 2015; Kumin, 2008; Laws, 2004; Rosin et al, 1988; Rupela et al, 2010; Yoder et al, 2016). It is very common among children with Down syndrome to display a muscle tone known as hypotonia, which means that children's muscles are loose and soft, which affects many aspects of their development, such as movement, strength and language development.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding articulation, research has shown that there is a variety in the development of the articulation skills in children with Down syndrome regarding their ability to properly articulate consonants and vowels and that they exhibit larger or smaller deviations from the typical population (Glenn & Cunningham, 2005; Katsarou & Andreou, 2017; Yoder & Warren, 2004). Among the most frequent phonological processes observed in children/adolescents with Down syndrome are the reduction of consonant clusters and the deletion of word‐final consonants (Cleland et al., 2010; Roberts et al., 2005; Rupela & Manjula, 2007; Rupela et al., 2010). Differences in the structure and functioning of articulators, such as tongue and palate, as well as muscle hypotonia, might affect speech production in individuals with Down syndrome (Abbeduto et al., 2007; Barnes et al., 2006; Kent & Vorperian, 2013; Stoel‐Gammon, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Differences in the structure and functioning of articulators, such as tongue and palate, as well as muscle hypotonia, might affect speech production in individuals with Down syndrome (Abbeduto et al, 2007;Barnes et al, 2006;Kent & Vorperian, 2013;Stoel-Gammon, 2001). Articulation deficits have been documented by several studies in the literature, which have found that phonological development is seriously affected in children and adolescents with Down syndrome (Cleland et al, 2010;Roberts et al, 2005;Rupela et al, 2010).…”
Section: Introductionmentioning
confidence: 99%